Exploring urban print environments: a comparative study across San Antonio and Santiago and implications for early childhood literacy practices. (10th October 2018) - Sailors, Misty; Orellana, Pelusa; Stortz, Rebecca; Sellers, Teresa
Abstract: In this study, we compared the types of texts found in two metropolitan areas (Santiago, Chile, and San Antonio, TX, USA) as a way of documenting the sponsorship of literacy within these two communities. We found (roughly) equal number of texts across the sites but interesting patterns within each. San Antonio's texts were primarily sponsored by industry and the military and Santiago's texts by political and religious sponsors. Similarly, there were statistically significant differences in the types of texts across neighbourhoods based on how well they were historically resourced. Our findings have implications for teaching early literacy through environmental print.